Kontribusi Kepemimpinan dan Faktor Iklim Kerja Terhadap Motivasi Kerja Tutor PKBM - Santosa, Tri Budi (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to determine the influence of leadership and work climate factors on the work motivation of tutors at the Community Learning Activity Center in Surakarta. This research uses quantitative methods. The research population was all PKBM tutors in Surakarta. The sampling technique used purposive sampling with a total sample of 15 tutors. Validation of the instrument uses the product moment correlation technique. Instrument reliability uses Cronbach's Alpha. The data analysis technique uses multiple linear regression. The research results show that: (1). Leadership contributes positively and significantly to increasing the work motivation of PKBM tutors in Surakarta (sig. 0.041). (2). The work climate contributes positively and significantly to increasing the work motivation of PKBM tutors in Surakarta (0.024). (3). Leadership and work climate contribute positively and significantly to increasing the work motivation of PKBM tutors in Surakarta (sig. 0.000).